Evaluation of Student Achievements in the National Pedagogical Theory and Practice of the Late Nineteenth - 40 Years of the Twentieth Century: Historiography and Sources of Research - Svitlana Ostapchuk (Pedagogical Discourse, 2013)
In this article  modern historiography and sources of unexplored problem of assessment of student achievements in the domestic educational theory and practice of the late nineteenth – 40 years of the twentieth century are analyzed. For the determination of the essence, forms, types, criteria, functions, methods of assessment of students’ progress in the elementary and secondary schools of the exploring period there such sources, as normative legal documents, periodicals of the late nineteenth – 40 years of the twentieth century, reports, brochures, textbooks for the pedagogues and representatives of education are systematized and generalized.